Analytical strategies for floating solar PV policy development in South Korea - Lee, Youhyun; Kim, Kyoungmin (Membrane and Water Treatment, 2022)
Using the SWOT-AHP method, this study identifies the priorities in the development of floating solar photovoltaics (PV) and suggests possible strategies. Our study analyzed the priorities in planning future solar PV strategies based on the opinions of 27 experts. Our results indicate that the government should expand support while emphasizing the benefit of floating solar PV in that it causes less environmental damage compared to onshore solar PV. In addition, the government should properly deal with the public-private conflict regarding the installation of floating solar PV. Floating solar PV itself has not reached a mature technological and institutional stage, but could be an option or alternative for saturated onshore solar PV facilities in Korea
Keywords: Analytical strategy; Floating photovoltaic; Floating solar pv; Korean energy policy; Photovoltaics; Policy development; Solar photovoltaics; Solar PVs; South Korea; Swot-ahp; Floating photovoltaic (fpv); Floating solar pv; Korean energy policy; Swot-ahp